Supported copper triflate as an efficient catalytic system for the synthesis of highly functionalized 2-naphthol Mannich bases under solvent free condition - Dindulkar, Someshwar D.; Puranik, Vedavati G.; Jeong, Yeon Tae (Tetrahedron Letters, 2012)
Various heterogeneous catalysts (Lewis acid) have been prepared and screened for the synthesis of Betti bases in an attempt to reduce the environmental hazards associated with the conventional homogeneous Lewis acid system. And we found especially Cu(OTf)(2)center dot SiO2 catalyzes the three-component coupling of aldehyde, 2-naphthol, and alicyclic amine to generate Betti base with high efficiency under neat conditions without additional co-catalyst or additive in air. The reaction is not sensitive to water and occurs smoothly in water as well. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Betti bases; single-crystal XRD; Solvent-free; Supported copper triflate; Three-component coupling